Performance analysis of different methods for optimal sliding mode control of DC/DC buck converter - Chlaihawi, Amer A.; Al-Modaffer, Ameen M.; Alhadrawi, Zaid (Institute of Advanced Engineering and Science, 2024)
Performance is always need to be considered in designing DC/DC buck converter. Despite the drastic use of DC/DC buck converter in industry, limitations due to unregulated voltage and current still persist. The dynamic performance of three methods of sliding mode control (SMC) were investigated. The comparative assessment of integral sliding mode control (ISMC) method, showed that the ISMC has an outstanding performance over the other tested methods of two variables with conventional SMC. The excellent performance of ISMC, under diverse operating conditions that include varying input voltage and load resistance, is achievable and it can provide a considerable edge over other control techniques in various field of industries, include electrical vehicle. The ISMC is highly preferable to overcome the problem of varying switching frequency, as well as optimizing power on transient response. The performance characteristic of ISMC shows fast dynamic response of various applications. Detailed simulations of the three SMC methods were carried out to validate the control algorithms using MATLAB/Simulink software.